Mapping the Intellectual Structure of Public Procurement and E-Procurement Adoption: A Bibliometric Analysis - O. O. Dwomoh; C. O. Aigbavboa; G. Kaku; F. Asare (AFRICAN JOURNAL OF APPLIED RESEARCH, 2026)
Purpose: This study examines the intellectual structure, thematic evolution, and knowledge development of research on public procurement and e-procurement adoption. Design/Methodology/Approach: The study employs a bibliometric research design based on 744 Scopus-indexed publications published between 2000 and 2026. Using the Biblioshiny interface within the Bibliometrix package, the study applies performance analysis and science mapping techniques to evaluate the field's development. Research Limitation: The bibliometric analysis was based exclusively on publications retrieved from the Scopus database and restricted to English-language publications. This may have influenced the representation of some authors, institutions and countries within the analysis. Findings: The findings reveal substantial growth in research on public procurement and e-procurement adoption over the study period. Sustainability, innovation, transparency, accountability, and digital transformation emerged as the dominant themes shaping the field. The study further identifies important conceptual and empirical gaps that warrant further scholarly attention. Practical Implication: The findings provide policymakers and procurement practitioners with insights for strengthening procurement governance, digital procurement reforms, and institutional accountability. Social Implication: Effective procurement and e-procurement systems can improve transparency, reduce procurement irregularities, and support sustainable public sector governance. Originality/Value: The study provides a comprehensive assessment of the intellectual structure and thematic development of public procurement and e-procurement adoption research while identifying emerging areas for future investigation.